Study of the effect of anaesthesia on the canine ultrasonographic optic nerve sheath diameter. (15th July 2021) - Drolet, C.; Pinard, C.; Gaitero, L.; Monteith, G.; Bateman, S.
Abstract : Objectives: To investigate the effects of anaesthetic duration and serial anaesthetic events on optic nerve sheath diameter in a population of dogs without intracranial disease using point‐of‐care ultrasonography. Materials and Methods: Client‐owned dogs requiring advanced head imaging were prospectively enrolled. Exclusion criteria included signs of elevated intracranial pressure, glaucoma and optic nerve disease. Using a transpalpebral technique, two optic nerve sheath diameter measurements were recorded for each eye at three timepoints: following premedication, after induction within 7 minutes and before discontinuing isoflurane. Mixed model analysis was used to characterise optic nerve sheath diameter behaviour and investigate the effects of anaesthetic duration, bodyweight and anaesthetic protocol, age and sex. Results: Fourteen dogs of various ages, breeds and bodyweights were enrolled. A positive linear relationship was detected between body weight and optic nerve sheath diameter. In 12 of 14 dogs, the optic nerve sheath diameter increased from measurements taken after premedication when compared to measurements taken after induction within 7 minutes. In a subset of patients, measurements subsequently decreased when anaesthetic duration exceeded 120 minutes. Age, side, sex, final body temperature, blood pressure and anaesthetic protocol did not significantly affect optic nerve sheath diameter. No significant association was noted between optic nerve sheath diameter and end‐tidal carbon dioxide after induction and before discontinuing isoflurane. Clinical Significance: When using point‐of‐care ultrasound, a transient increase in optic nerve sheath diameter occurs between premedication and within 7 minutes following induction, regardless of bodyweight. This should be taken into consideration when serial monitoring is performed.